Regular monitoring of post-training biochemical markers as a tool for injury prevention in professional athletics – review - Szydłowska, Sara; Błaszków, Krzysztof; Elias, Jagoda; Biesiada, Wiktor; Zubiak, Marlena; Kaźmierczak, Dominika (Quality in Sport, 2025)
Modern professional sports place increasingly high demands on athletes, necessitating the optimization of training loads and effective injury prevention. One of the key tools supporting these processes is the regular monitoring of biochemical markers, which allows for the assessment of the body’s response to physical exertion and the detection of overtraining states. This paper discusses the significance of selected biochemical indicators, including creatine kinase (CK), lactate dehydrogenase (LDH), acute-phase proteins (CRP, IL-6, IL-8, IL-10, haptoglobin), metallothionein (MT), electrolytes, and hormones (testosterone and cortisol), in the context of monitoring fatigue, recovery, and injury risk. Analysis of available studies has shown that the integration of various biomarkers enables a more precise assessment of the body’s adaptation to training loads and the early detection of overtraining symptoms. At the same time, attention has been drawn to individual physiological differences affecting the interpretation of results, as well as the need for further research into the standardization of measurement methods. Regular monitoring of biochemical markers can serve as an effective tool for optimizing the training process, provided it is integrated with an individualized approach to the athlete and considers a broad spectrum of factors influencing the body’s response. The implementation of such an approach can contribute to minimizing injury risk, improving performance, and enhancing recovery efficiency, which is crucial for the long-term professional development of athletes.